1998
DOI: 10.1177/073490419801600202
|View full text |Cite
|
Sign up to set email alerts
|

The Initiation of Smolderin Combustion in Cellulosic Fabrics

Abstract: The time and heat flux required for the initiation of smoldering combustion in cellulosic fabrics depends on the properties of both the environment and the fabric. In the environment, there must be sufficient oxygen to support smoldering combustion and there must be sufficient heat to raise the temperature of the fabric to the point where combustion becomes self supporting. The critical factors for the cellulosic fabrics are the potassium and/or sodium ion content and the thermal characteristics of the fabric.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…The results are consistent with those reported by Kellogg et al [12]. He indicated that high contents of K and Na (around 1500-2500 ppm) assist fabric combustion.…”
Section: Correlation Between Metallic Content and Characteristics Of supporting
confidence: 92%
See 1 more Smart Citation
“…The results are consistent with those reported by Kellogg et al [12]. He indicated that high contents of K and Na (around 1500-2500 ppm) assist fabric combustion.…”
Section: Correlation Between Metallic Content and Characteristics Of supporting
confidence: 92%
“…Additionally, for fabrics with potassium and sodium ion contents in the range of approximately 1500-2500 ppm, the sensitivity to environmental factors increased [12]. Byung et al [13] found that cellulose with NaCl shows a high laevoglucose burning decomposition rate, and a fast conversion rate of heavy initial products to CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…These factors agree with the understanding that smouldering ignition is affected by the degree to which the total system is adiabatic. The time and heat flux required for the initiation of smouldering was also found to depend on the environment and the properties of the fabric (Kellogg et al 1998;Yi et al 2001). However, different results were obtained by different test laboratories as to the degree of correlation with cigarette type, and up to three quarter of the 79 upholstery fabrics produced similar ranking with the cotton duck fabrics used Eberhardt et al 1997;Hirschler 1997aHirschler , 1997bWanna & Zelius 2001;Wanna & Chen 2001;Ihrig et al 1987).…”
Section: Fabric and Substrate Parametersmentioning
confidence: 95%
“…Regardless of the lack of a standard test, early studies examining the fabric-cigarette interaction found that there is a correlation among the thermal characteristics of the burning cigarette, the total sodium and potassium content of the fabric, the mass of the fabric near the cigarette burning zone, and the extent of oxygen diffusion through the fabric to the cigarette burning zone (Wu et al 1992;Dwyer et al 1994;Lewis et al 1995aLewis et al , 1995bKellogg et al 1998;Spears et al 1995). These factors agree with the understanding that smouldering ignition is affected by the degree to which the total system is adiabatic.…”
Section: Fabric and Substrate Parametersmentioning
confidence: 99%
“…Additionally, for fabrics with potassium and sodium ion contents in the range of ϳ1500 -2500 ppm (weight/weight), the sensitivity to environmental factors increased. 15 NaCl, a smoldering combustion enhancer, slightly stabilizes the pyrolysis of cellulose. 16 Previous studies so far have only discussed the characteristics of pollutants induced by incense burning.…”
Section: Introductionmentioning
confidence: 99%